2009
DOI: 10.1007/s00595-008-3805-8
|View full text |Cite
|
Sign up to set email alerts
|

Carcinosarcoma of the gallbladder: Report of a case

Abstract: Gallbladder carcinosarcoma is one of the rarest subsets of gallbladder malignancies. To date, only 34 cases have been reported in the English literature. Therefore the knowledge and experience regarding this disease is limited. This report describes a 70-year-old male patient who was diagnosed by documenting the epithelial and mesenchymal components with histopathological and immunohistochemical methods, and treated by a radical cholecystectomy. The pediculated polypoid tumor had filled the lumen, originating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 12 publications
1
25
1
Order By: Relevance
“…Carcinosarcoma of the gallbladder is a rare tumour, with only 34 cases being reported in the English literature [2]. It is characterized by a malignant trasformation of both the epithelial and the mesenchymal components of the same tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carcinosarcoma of the gallbladder is a rare tumour, with only 34 cases being reported in the English literature [2]. It is characterized by a malignant trasformation of both the epithelial and the mesenchymal components of the same tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of the tumour in many different organs which include the uterus, lung, oesophagus, kidney and pancreas is well known [1]. However, the gallbladder is a rare site, with only 34 cases being reported in the English literature till date [2]. A vast majority of the gallbladder (GB) cancers are adenocarcinomas, with carcinosarcomas accounting for fewer than 1% of the tumours [3].…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the anatomic position of the GB and vague symptoms [4,5]. Although recent studies suggest some causative factors such as multistep genetic alterations, the precise mechanism of GB carcinogenesis remains unclear [6]. Many studies have suggested the presence of cholecystolithiasis is one of the most important risk factors for CGB [7].…”
Section: Discussionmentioning
confidence: 99%
“…He underwent a radical cholecystectomy and hepatodudodenal ligament lymphadenectomy once it was discovered that he had a malignant mesenchymal tumour on frozen section [6]. On the other hand, an 81 year old male, with CSGB invading the liver, underwent cholecystectomy with liver segmentectomy and lymph node dissection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation